Analisis Mata Kuliah Peminatan Prodi Sistem Informasi Terhadap Semester 6 Universitas Islam Negeri Sumatera Utara - Pratama, Ikhsan; Nur, Suci Fadhilah; Ardiyansyah, Rifky; Meliani, Wiza Sintia; Harianto, Dannis Risya; Nasution, Adelyna Oktavia (Indo-MathEdu Intellectuals Journal, 2025)
This research analyzes the trend of course selection among sixth semester students of the Information Systems Study Program at the Islamic University of North Sumatra (UINSU). The method used is descriptive quantitative with a survey approach. Data was collected through an online questionnaire distributed using Google Form. The resulting data was analyzed descriptively quantitatively. The results show that the majority of students chose Big Data Analytics, which is (50%) out of (100%), where 25 out of 50 students who completed the survey chose Big Data Analytics. This is followed by Multimedia (34%) and Artificial Intelligence (16%). The main factors for choosing are personal interest and relevance to career prospects. Big Data Analytics is considered the most challenging, yet it also aligns best with student expectations. This finding underscores the need for adaptive curriculum development and directed academic guidance so that specializations are more relevant to industry needs and student interests